Developing Animated Videos as Kemuhammadiyahan Learning Media - Habibi, Muhammad; Asrori, Asrori; Rusman, Rusman (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
This study aimed to develop, test the feasibility, and evaluate the usefulness of animated videos as learning media for elementary school students in the Kemuhammadiyahan subject. This research employed the Research and Development method with five stages: Analyze, Design, Development, Implementation, and Evaluation (ADDEI model). Data for the current research were gathered through observation, interviews, questionnaires, and documentation. Material and media experts were involved in product validation tests to test the product's feasibility. The product usability test was conducted using a questionnaire instrument administered to 10 students in the small-scale trial and 31 in the large-scale trial. The product validation obtained a percentage of 85% from the material expert and 87% from the media expert, both in the valid categories. Based on the responses of 10 students in the small-scale trial, the product attractiveness test results were 83.45% or very interesting. The product's attractiveness value was 87.86%, or very interesting, in a large-scale trial of 31 students. As a result, research on the development of animated video media on the Kemuhammadiyahan subject for elementary school students was very feasible in learning Kemuhammadiyahan.